Empathy and Offending, a Study About the Role of Cognitive and Affective Empathy in Sexual Violence - Gijsbers, Elke (International journal of offender therapy and comparative criminology, 2025)
Plain language summaryUnderstanding Empathy in Sexually Violent OffensesEmpathy problems are often observed in people with a history of criminal behavior, including sexual offenses. However, research suggests that lacking empathy is not a major cause of sexual offending. Instead, it is linked to other factors that increase risk, like having attitudes that support offenses or being hostile. Most studies do not separate two types of empathy: cognitive empathy (understanding others’ emotions) and affective empathy (feeling emotional resonance). Without this distinction, it is hard to pinpoint what kind of empathy issues exist in offenders, particularly those with sexual offenses. This study examined the role of these two types of empathy in three groups: men convicted of sexual offenses, men convicted of violent offenses, and men from the general population. Researchers measured empathy levels using a specific questionnaire and adjusted for impulsivity. The results showed that men with sexual offenses had higher levels of both cognitive and affective empathy compared to those with violent offenses. When compared to the general population, they only scored higher on affective empathy. This suggests that empathy issues in sexual offenders are more complicated than they might seem. However, the fact that the data came from self-reports may have influenced the findings.